2012
DOI: 10.1186/1471-2458-12-203
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and health-related quality of life in English general population: implications for economic evaluations

Abstract: BackgroundLittle is known as to how health-related quality of life (HRQoL) when measured by generic instruments such as EQ-5D differ across smokers, ex-smokers and never-smokers in the general population; whether the overall pattern of this difference remain consistent in each domain of HRQoL; and what implications this variation, if any, would have for economic evaluations of tobacco control interventions.MethodsUsing the 2006 round of Health Survey for England data (n = 13,241), this paper aims to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
5
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(115 citation statements)
references
References 57 publications
5
102
5
3
Order By: Relevance
“…We found a consistent dose-response relationship between smoking status, determined by number of cigarettes smoked, and lower SF-6D utility score across the three cohorts, which were supported by previous research on the SF-6D [11 ], EQ-5D [40] and HRQoL [41]. Although these findings contrast other studies [14,15], the differences observed may be due to differences in the number of levels used to classify smoking patterns.…”
Section: Discussioncontrasting
confidence: 55%
“…We found a consistent dose-response relationship between smoking status, determined by number of cigarettes smoked, and lower SF-6D utility score across the three cohorts, which were supported by previous research on the SF-6D [11 ], EQ-5D [40] and HRQoL [41]. Although these findings contrast other studies [14,15], the differences observed may be due to differences in the number of levels used to classify smoking patterns.…”
Section: Discussioncontrasting
confidence: 55%
“…For example, Poortinga et al [7] compared public perceptions of climate change and energy futures between Britain and Japan before and after the Fukushima accident, because of existing data from public perceptions surveys carried out in Britain and Japan before [8] and after [9] the accident. Vogl et al [10] show how data from the Health Survey for England [11] could be analysed to inform public health strategies, in particular providing evidence that smoking negatively affects healthrelated quality of life. Regarding research methods, Ogden and Cornwell [12] show by analysing 400 interview questions and their corresponding responses from 10 qualitative studies in the area of health that the richness of interview data can be predicted by open questions, being located later on in an interview and being framed in the present or past tense.…”
Section: Social Sciences Data Reuse and Valuementioning
confidence: 99%
“…84 Utility values based on current smoking status (current or former smoker) were derived from the Health Survey for England adjusted for relevant covariates including disease prevalence. 85 The EuroQol-5 Dimensions, a validated instrument for measuring health-related quality of life, was used for both sets of utility values and UK tariffs were used for calculating utility scores 86 (see Appendix 1, Table 38). …”
Section: Utility Valuesmentioning
confidence: 99%